Statin Effects on Exacerbation Rates, Mortality, and Inflammatory Markers in Patients with Chronic Obstructive Pulmonary Disease: A Review of Prospective Studies. Issue 5 (13th April 2016) - Howard, Meredith L.; Vincent, Ashley H.
Abstract : Chronic obstructive pulmonary disease (COPD) is a debilitating, irreversible disease with currently available therapies targeting symptom control and exacerbation reduction. A need for alternative disease‐modifying therapies remains, specifically those that may have antiinflammatory and immunomodulatory properties that impact the pathophysiologic components of COPD. Statin drugs, the current gold standard for the treatment of dyslipidemia and prevention of cardiovascular disease (CVD), contain properties that affect the inflammatory disease processes seen in COPD. Several retrospective studies have demonstrated that statins may have a benefit in the reduction of morbidity and mortality in patients with COPD. This has led to prospective trials evaluating the impact of statins on various COPD‐related outcomes. This article reviews the current body of prospective evidence for use of statins in patients with COPD. A search of the PubMed/Medline database of English‐language articles was conducted from 1964 through November 2015; references of relevant articles were also reviewed for qualifying studies. Prospective studies of all types relating to statin use in patients with COPD were included if they had COPD‐ or respiratory‐related outcomes; ultimately, eight studies were identified for this review. Statin effects on exacerbation rates, mortality, and inflammatory markers in patients with COPD are discussed. Strong prospective evidence does not currently exist to suggest that statins provide a clinical benefit in patients with COPD who do not have other CVD risk factors. Benefits from statins that have been illustrated are likely explained by their impact on underlying CVD risk factors rather than the COPD disease process. An opportunity exists for unanswered questions to be addressed in future studies.